Zero desiccant carryover in liquid desiccant dehumidification system - Tan, Jasper Kian Ann (2018)
ACMV industry has developed rapidly in the recent years around the world. That is due to the increase in demand for air-conditioners. Based on a statistics report, the world is about to install 700 million air-conditioners by 2030. As air-conditioners is well known for its high energy consumption, there will be a huge increase in energy usage which will eventually harm the environment. However, there is the new liquid desiccant dehumidification system technique which will remove humidity with far less energy input than conventional cooling coils. Liquid desiccant dehumidification system is an efficient system for application in industrial, commercial, institutional, and green facilities, where cool and dry air is needed. With the increase in demand for air-conditioning system and the new LDDS technique, it is important to ensure the safety of the system for customers’ usage in physical aspect, the processed air quality. Although LDDS has great advantages as compared to conventional air-conditioning system which is mainly the drop in energy consumption and its efficiency, it uses liquid desiccant to get the job done. The liquid desiccant is used to absorb moisture in the air, this process may cause the air to carry chemical drops of the liquid desiccant which may cause harm to the skins of human beings. Given this information and the interest of ACMV, it is necessary to evaluate and analyze the newly developed LDDS for further improvement. Mainly to ensure there is zero desiccant being carried over with the fresh air. This final year project (FYP) report documents the investigation of output air quality of the liquid desiccant dehumidification system. Main focus will be placed on the liquid desiccant temperature and the air flow rate of the system.